Photodegradation Kinetics of Phenol and Methylene Blue Dye Present in Water Stream Over Immobilized Film Ti02 Catalyst - Chin Mei Ling; Abdul Rahman Mohammed; Subash Batia (ASEAN Journal of Chemical Engineering, 2005)
A photocatalytic reactor has been designed to study the kinetics of photocatalytic degradation of phenol and methylene blue dye present in water stream on immobilized Ti02 catalyst. The principal part of the reactor consisted of a cylindrical pyrex glass tube whose outer surface was coated with the synthetic Ti02 film catalyst prepared from sol-gel technique. An ultraviolet light lamp of 365 nm wavelength was set longitudinally in the center of the tube. The synthetic Ti02 film formulation with the molar ratio of 1 titanium isopropoxide : 8 isopropanol: 1.1 H20: 3 acetyl acetone: 0.05 acetic acid was used to develop the immobilized Ti02 film catalyst deposited over the glass support. The performance of the immobilized photocatalytic reactor was evaluated by studying the decomposition kinetics of phenol and methylene blue dye present in the aqueous stream. The kinetics of photocatalytic degradation of phenol and methylene blue obeyed first order heterogeneous equation. The kinetic parameters were evaluated from the kinetic data using the Langmuir"Hinshelwood-Hougen-Watson (LHHW) model. Keywords: Kinetics, methylene blue, phenol, photocatalytic reactor, and Ti02 film catalyst.